Pulmonary Arterial Thrombosis in COVID-19 With Fatal Outcome: Results From a Prospective, Single-Center, Clinicopathologic Case Series - Lax, Sigurd F. (Ann Intern Med, 2020)
BACKGROUND: Coronavirus disease 2019 (COVID-19) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly become pandemic, with substantial mortality. OBJECTIVE: To evaluate the pathologic changes of organ systems and the clinicopathologic basis for severe and fatal outcomes. DESIGN: Prospective autopsy study. SETTING: Single pathology department. PARTICIPANTS: 11 deceased patients with COVID-19 (10 of whom were selected at random for autopsy). MEASUREMENTS: Systematic macroscopic, histopathologic, and viral analysis (SARS-CoV-2 on real-time polymerase chain reaction assay), with correlation of pathologic and clinical features, including comorbidities, comedication, and laboratory values. RESULTS: Patients' age ranged from 66 to 91 years (mean, 80.5 years; 8 men, 3 women). Ten of the 11 patients received prophylactic anticoagulant therapy; venous thromboembolism was not clinically suspected antemortem in any of the patients. Both lungs showed various stages of diffuse alveolar damage (DAD), including edema, hyaline membranes, and proliferation of pneumocytes and fibroblasts. Thrombosis of small and mid-sized pulmonary arteries was found in various degrees in all 11 patients and was associated with infarction in 8 patients and bronchopneumonia in 6 patients. Kupffer cell proliferation was seen in all patients, and chronic hepatic congestion in 8 patients. Other changes in the liver included hepatic steatosis, portal fibrosis, lymphocytic infiltrates and ductular proliferation, lobular cholestasis, and acute liver cell necrosis, together with central vein thrombosis. Additional frequent findings included renal proximal tubular injury, focal pancreatitis, adrenocortical hyperplasia, and lymphocyte depletion of spleen and lymph nodes. Viral RNA was detectable in pharyngeal, bronchial, and colonic mucosa but not bile. LIMITATION: The sample was small. CONCLUSION: COVID-19 predominantly involves the lungs, causing DAD and leading to acute respiratory insufficiency. Death may be caused by the thrombosis observed in segmental and subsegmental pulmonary arterial vessels despite the use of prophylactic anticoagulation. Studies are needed to further understand the thrombotic complications of COVID-19, together with the roles for strict thrombosis prophylaxis, laboratory, and imaging studies and early anticoagulant therapy for suspected pulmonary arterial thrombosis or thromboembolism. PRIMARY FUNDING SOURCE: None.